Song after song : the musical life of Julie Andrews - Hedlund, Julie (Little Bee Books, 2023)
This picture book biography chronicles the early life of the beloved film star, theater performer, singer and published author, showing how she found her extraordinary voice when her stepfather taught her to sing to comfort her and fill her time during the London Blitz.